2021
DOI: 10.7573/dic.2021-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins, supplements and COVID-19: a review of currently available evidence

Abstract: Background In the midst of the COVID-19 pandemic, there has been an information overload of health data (both accurate and inaccurate) available to the public. With vitamins and supplements being readily accessible, many have turned to using them in an effort to combat the virus. The purpose of this review was to analyse clinical trials regarding vitamins and supplements for the treatment of COVID-19 infections. Methods Articles were identified through a literature sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 80 publications
(58 reference statements)
3
21
0
6
Order By: Relevance
“…Such deficiencies can be corrected by following a healthy diet combined with the proper use of supplements. Although the use of vitamin and mineral supplements does not prevent infection with COVID-19 [ 12 ], it can improve immune status and subsequent disease severity [ 13 , 14 ]. Hence, the use of supplements has increased drastically during the COVID-19 pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such deficiencies can be corrected by following a healthy diet combined with the proper use of supplements. Although the use of vitamin and mineral supplements does not prevent infection with COVID-19 [ 12 ], it can improve immune status and subsequent disease severity [ 13 , 14 ]. Hence, the use of supplements has increased drastically during the COVID-19 pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamins C and D are widely administrated to SARS-CoV-2 infected patients, and as prophylaxis against COVID-19 infection [ 20 ]. Some clinical studies found that these Vits have favorable effects among SARS-CoV-2 infected patients [ 21 ]. Therefore, this study investigated the influence of Vit C and D on the mRNA expression of SARS-CoV-2 entry genes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the epidemiological findings, vitamin D is essential for reducing acute respiratory diseases. Besides, vitamin D can be prescribed to have antiviral effects as a preventive or therapeutic approach as an adjuvant in COVID-19 infections [131] , [132] , [133] . Vitamin D is involved in a wide range of cellular processes, including dipeptidyl peptidase-4 receptor (DPP-4/CD26) binding, recognition of RIG-I host, and Papain-like protease (PLpro).…”
Section: Vitamin Dmentioning
confidence: 99%